SYNTHESIS, STRUCTURAL AND THEORETICAL INVESTIGATION OF SOME NEW SCHIFF BASES AND 1,3,4-OXADIAZOLE COMPOUNDS DERIVED FROM LAURIC ACID - MAHMOOD, MAHMOOD HAMEED; SADALDIN, MUHEB A. (Journal of Duhok University, 2023)
New Schiff bases derivatives from lauric acid were synthesized through the condensation of dodecane methyl ester with hydrazine to give corresponding hydrazide, which react with aromatic aldehyde derivatives to afford dodecanehydrazide-hydrazones derivatives and with carbon disulfide to give 1,3,4-oxadiazole-2-thion. The chemical structures were confirmed by numerous characterization methods; including Infrared, Ultraviolet-Visible, 1H and 13C Nuclear Magnetic Resonance (NMR) measurements. In order to investigate the 1H and 13C Nuclear Magnetic Resonance, vibrational frequencies, Ultraviolet visible spectra, optimized molecular geometry, HOMO & LUMO and other spectroscopic properties, Density Functional Theory (DFT/B3LYP/6-311++G(d,p)) stimulations were carried out